Research on the Collaborative Education Model of "Ideological and Political Education in the Curriculum" and "Ideological and Political Courses" in Finance and Economics Universities - Huang, Yan (International Journal of Social Sciences and Public Administration, 2024)
The research on the collaborative education model of "Ideological and Political Education in the Curriculum" and "ideological and political courses" in financial and economic universities is an important content of ideological and political work in universities. This article takes the research on the collaborative education model of "Ideological and Political Education in the Curriculum" and "ideological and political courses" in financial and economic universities as the starting point from the perspective of "cultivating morality and talents". Combining with the current situation of ideological and political education in financial and economic universities, it explores the construction of a collaborative education model of "Ideological and Political Education in the Curriculum" and "ideological and political courses" in financial and economic universities with value shaping as the goal, ability cultivation as the focus, and seeking true knowledge and practical results in practice.